2022
DOI: 10.1021/acs.jpcc.2c02371
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Precipitation of Zeolitic Imidazolate Frameworks in a Gelled Medium

Abstract: Formation of spatially periodic patterns is a ubiquitous process in nature and man-made systems. Periodic precipitation is the oldest type of pattern formation, in which the formed colloid particles are self-assembled into a sequence of spatially separated precipitation zones in solid hydrogels. Chemical systems exhibiting periodic precipitation mostly comprise oppositely charged inorganic ions. Here, we present a new sub-group of this phenomenon driven by the diffusion and reaction of several transition metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…According to this behavior, LP could be employed for practical purposes to track the polarity changes in unknown solvents, similar to the use of LPs for tracking environmental changes. ,, Moreover, tuning the solvent polarity can be a promising strategy to control, tailor, and design both regular LPs and new hierarchical structures. In addition, hierarchical layered structures are of great importance for the design of self-organized functional materials from nano- to macroscale. Some recent studies showed that LPs can be formed using some functional materials (e.g., metal nanoparticles and metal–organic frameworks), and another study indicated how to form microscale periodicity. ,,, By combining this knowledge with our strategy of polarity-based LP control, LP could be a potential candidate for the generation of self-organized hierarchical layered structures with various functions and structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this behavior, LP could be employed for practical purposes to track the polarity changes in unknown solvents, similar to the use of LPs for tracking environmental changes. ,, Moreover, tuning the solvent polarity can be a promising strategy to control, tailor, and design both regular LPs and new hierarchical structures. In addition, hierarchical layered structures are of great importance for the design of self-organized functional materials from nano- to macroscale. Some recent studies showed that LPs can be formed using some functional materials (e.g., metal nanoparticles and metal–organic frameworks), and another study indicated how to form microscale periodicity. ,,, By combining this knowledge with our strategy of polarity-based LP control, LP could be a potential candidate for the generation of self-organized hierarchical layered structures with various functions and structures.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 Some recent studies showed that LPs can be formed using some functional materials (e.g., metal nanoparticles and metal–organic frameworks), and another study indicated how to form microscale periodicity. 17 , 20 , 54 , 55 By combining this knowledge with our strategy of polarity-based LP control, LP could be a potential candidate for the generation of self-organized hierarchical layered structures with various functions and structures.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction–diffusion (RD) systems, such as chemical gardens, precipitation pulses, biomorphs, and Liesegang patterns, have attracted a great deal of attention owing to the resultant pattern diversity, complex morphology, and spectacular self-assemblies. However, recent trends in the studies of RD are due to the revelation that it can be employed as a simple, facile, green, and one-pot method for novel material synthesis of micro- and nanoparticles of the inorganics and metal–organic frameworks with hierarchical particle sizes, especially in the case of Liesegang patterns (LPs). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liesegang experiments involving the formation of organic and organometallic materials, metal–organic frameworks (MOFs), and zeolitic imidazolate frameworks (ZIFs) have been reported; however, such reports are relatively scarce. The main reason for this could be that the mechanism of pattern formation involving organics or bulky molecules as one of the reactants could not be explained based on the “diffusion–reaction–solubility product–supersaturation–aggregation–precipitate deposition” nexus in addition to that of the complexity of handling organic materials, especially for diffusion.…”
Section: Introductionmentioning
confidence: 99%